ASSOCIATIVE-VERBAL NETWORKS OF THE CONCEPT OLD AGE IN THE LINGUISTIC CONSCIOUSNESS OF NATIVE SPEAKERS OF RUSSIAN (Scientific journal of the Fergana State University, 2026)
The article examines the associative-verbal networks of the concept “OLD AGE” in the linguistic consciousness of native Russian speakers. Based on data from associative dictionaries, primarily the Russian Associative Dictionary by S.A.Sharov, as well as the principles of cognitive linguistics and cultural studies, the study analyzes the structure of associative reactions, their topology, emotional-evaluative range, and cognitive mechanisms. It is established that the concept “OLD AGE” is organized as a complex network of interconnected imagistic, social, temporal, physiological, and axiological elements that reflect the ambivalent perception of late age in Russian culture. The associative networks form a multilayered system of meanings including the biological and physiological aspects of aging, the social status of elderly people, emotional responses, and cultural stereotypes. The study demonstrates that the concept has a high density of associative links and represents a cultural constant of the national worldview.